HUBUNGAN PENGETAHUAN TENTANG COVID-19 DENGAN PERILAKU PENCEGAHAN PENULARAN COVID-19 PADA MASYARAKAT DI KELURAHAN ALANG-ALANG LEBAR PALEMBANG - Tini Yurika (Jurnal Kesehatan dan Pembangunan, 2022)
Indonesia is currently battling the corona virus outbreak which has caused millions of Indonesians to experience illness and thousands more to die. The government has appealed to the public to implement health protocols, namely maintaining a minimum distance of 1 meter, wearing masks, washing hands frequently, staying away from crowds and limiting mobility. This study aims to analyze the relationship between knowledge about covid-19 and behavior to prevent transmission of covid-19. This research used descriptive analytic method with cross sectional design. The population in this study was the entire community of Alang-alang Lebar Palembang Village with a total sample of 58 people. The sampling technique used was accidental sampling. The analysis that will be used is descriptive analysis and bivariate analysis. Keywords: Knowledge, Preventive Behavior, Covid-19